2003
DOI: 10.1200/jco.2003.05.191
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Neuroblastoma in Children Older Than One Year at Diagnosis: Comparable Results With Three Consecutive High-Dose Protocols Adopted by the Italian Co-Operative Group for Neuroblastoma

Abstract: The therapeutic modifications adopted in the ICGNB-89 and ICGNB-92 protocols were not associated with a significant improvement in response rate or in the 5-year OS and EFS as compared with the ICGNB-85 protocol. Attempts at intensifying chemotherapy were associated with greater toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 27 publications
(10 reference statements)
5
105
1
Order By: Relevance
“…We selected a particularly aggressive tumor line (NXS2) that models neuroblastoma (NB), the most common extracranial solid tumor and the first cause of lethality in preschool-age children. Advanced NB patients, who represent Ϸ50% of the cases, show metastatic dissemination at diagnosis and have a long-term survival rate of only 20% despite aggressive chemotherapy with autologous hematopoietic stem cell support (28,29).…”
Section: Short-term Starvation Prevents the Death Of Mice But Not Of mentioning
confidence: 99%
“…We selected a particularly aggressive tumor line (NXS2) that models neuroblastoma (NB), the most common extracranial solid tumor and the first cause of lethality in preschool-age children. Advanced NB patients, who represent Ϸ50% of the cases, show metastatic dissemination at diagnosis and have a long-term survival rate of only 20% despite aggressive chemotherapy with autologous hematopoietic stem cell support (28,29).…”
Section: Short-term Starvation Prevents the Death Of Mice But Not Of mentioning
confidence: 99%
“…1 Before the routine use of immunotherapy, 3-5 year progression-free survival (PFS) rates in national studies were 20-40%, [2][3][4][5][6] even with inclusion of patients with what is now known to be intermediate-risk NB. 7 The randomized study of the Children's Oncology Group showed significantly better outcome in patients treated post-ASCT with the anti-G D2 chimeric mAb ch14.18 plus granulocyte-macrophage colony-stimulating factor (GM-CSF) plus interleukin-2.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Features associated with an improved prognosis include younger age 5,7 and absence of bone marrow involvement at diagnosis, 12 early disease response 13 and a complete or near complete response following induction therapy. 6,7,10,14 A poorer prognosis has been associated with an elevated serum ferritin (4143 ng/ ml), 6 bone and BM metastasis, 6 detectable circulating NB cells at diagnosis, 15,16 persisting skeletal and BM disease at the end of induction therapy, 1,2 circulating NB cells in patients otherwise apparently disease-free 16 and high-level of NB contamination at marrow harvest.…”
Section: Introductionmentioning
confidence: 99%